The use of WhatsApp group discussion to improve students’ writing achievement - Wahyuni, Sri; Febianti, Kurnia (Program Studi Adminsitrasi Pendidikan Universitas Jambi, 2019)
The aim of this study was to find out whether the use of WhatsApp group could improve students’ ability in English writing achievement. The population of the study covered all of the second semester students of English study program in STKIP Muhammadiyah Pagaralam. Fourty students were selected purposively from all the population. The researcher used Quasi-experimental as the research methodology. To collect the data, written test was used to measure the students’ achievement in English writing. The data were analyzed by using paired sample t-test and independent sample t-test. The result of data analysis showed that the students obtained better improvement in English writing ability after being treated by using WhatsApp group discussion. Based on the result of independent t-test, the t value obtained was 5.298 and the significance level was p <.001. Futhermore, it can be concluded that there was a significant difference between the students who were taught through WhatsApp group discussion and those who were not. The students were interested in using WhatsApp group as media of learning especially in English writing. During the discussion in the WhatsApp group, they could get input such as new knowledge, better grammar, and improved vocabulary. WhatsApp group is a good way to be used as a teaching media especially in increasing students’ writing achievement.